2016
DOI: 10.1007/s13365-016-0504-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cellular HSV-1 receptor expression in human brain

Abstract: Herpes simplex virus type 1 (HSV-1) is a neurotropic virus linked to a range of acute and chronic neurological disorders affecting distinct regions of the brain. Unusually, HSV-1 entry into cells requires the interaction of viral proteins glycoprotein D (gD) and glycoprotein B (gB) with distinct cellular receptor proteins. Several different gD and gB receptors have been identified, including TNFRSF14/HVEM and PVRL1/nectin 1 as gD receptors and PILRA, MAG, and MYH9 as gB receptors. We investigated the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…In 1982, Ball first suggested that HSV-1 might be involved in the pathogenesis of AD by finding that the brain regions damaged in HSV encephalitis, the limbic system, are the same as those affected the earliest in AD [35]. This is reinforced by the finding that receptors for HSV-1 are selectively expressed in the limbic system [36]. Several other studies have shown that HSV-1 and being a carrier of the apolipoprotein E allele 4 (ApoE e4) together confer risk for AD [9,11,27,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…In 1982, Ball first suggested that HSV-1 might be involved in the pathogenesis of AD by finding that the brain regions damaged in HSV encephalitis, the limbic system, are the same as those affected the earliest in AD [35]. This is reinforced by the finding that receptors for HSV-1 are selectively expressed in the limbic system [36]. Several other studies have shown that HSV-1 and being a carrier of the apolipoprotein E allele 4 (ApoE e4) together confer risk for AD [9,11,27,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…HSV-1 has been implicated in AD pathogenesis by several lines of evidence, including the presence of HSV-1 viral DNA in human brain tissue [51,52], increased HSV-1 seropositivity in AD cases [53][54][55][56], the correlation of high avidity HSV-1 antibodies with protection from cognitive decline [56], the binding of HSV-1 gB to APOE-containing lipoproteins [57], HSV-1-induced amyloidogenic processing of amyloid precursor protein (APP) [58][59][60], and preferential targeting of ADaffected regions in HSV-1 acute encephalitis [61]. In addition, HSV-1 gD receptors and gB receptor PILRA increase with age in multiple brain regions, including the hippocampus [62]. Additional AD risk loci have been proposed to play a role in the life cycle of HSV-1 [63], including CR1, which is capable of binding HSV-1 [64].…”
Section: Discussionmentioning
confidence: 99%
“…Lathe and Haas ( 2017 ) found increased expression of host cell viral entry receptors for HSV-1 glycoproteins gD and gB within the hippocampus using gene expression profiling from the microarray based Allen Human Brain Atlas and Human Brain Transcriptome database. The hippocampus demonstrated significantly increased gene expression of host cell viral entry receptor proteins PVRL1, TNFRFS14 and MYH9 when tested across the whole human brain.…”
Section: The Hsv-1 Alzheimer’s Disease Hypothesismentioning
confidence: 99%